A cross sectional study on vaccination coverage of COVID-19 in rural slums of field practice area of a medical college in Hyderabad - Hussain, Nadia Mouzzam; Neeluri, Rajesh; Ahmad, Sultan Rizwan (International Journal Of Community Medicine And Public Health, 2024)
Background: The COVID-19, a global pandemic, first identified in the Hubei province (Wuhan), China in December, 2019 is caused by SARS-CoV-2. Attempts of containing it there failed, causing it to spread to other regions of Asia and eventually around the whole world in 2020. To control the risk of transmission, non-pharmaceutical interventions were taken up by the governments all over the world. Subsequently, vaccines were developed which were administered. Vaccine hesitancy has become a significant barrier in various countries due to expeditious pace of vaccine development. Hence, this study was conducted to estimate the COVID-19 vaccination coverage in rural slums of field practice area of a medical college in Hyderabad. Methods: A community based cross sectional study was conducted between January 2023 to March 2023 in field practice area of RHTC of a medical college in Hyderabad. Data was collected from 400 eligible participants, who were selected by simple random sampling, using a predesigned, pretested structured questionnaire. Data was entered in Microsoft Excel and analysed using SPSS Version 20. Chi square test was applied. Results: In the present study, 60% of the study participants had taken COVID vaccine. Vaccination coverage was high i.e., 65.35% among 18-28 years of age group, 82.2% in females, 62.66% in Muslims, 85.71% in graduates, 80.90% in semi-skilled workers and 77.77% in upper middle socioeconomic class. Conclusions: The COVID-19 vaccination coverage was low in rural slums. Age, gender, religion, education, occupation and socioeconomic status are important determinants of COVID-19 vaccination.